Meningkatkan Hasil Belajar Lari Cepat Dengan Permainan Speed Colour (Department of Physical Education, Sport, Health and Recreation, 2015)
The aim in this study was to determine the effectiveness of the learning game Speed Colour to increase learning outcomes sprint. This research is a class action (Classroom Action Research), conducted in two cycles. Each cycle has four steps: planning, implementation, observation, and reflection. Subjects were students of class V Government Elementary School Dewi masyithoh 02 Banyumudal Moga District of Pemalang in the second semester of academic year 2013/2014, the number of students 30 with details of the number of male students and 16 female students 14.Hasil study showed that the administration model of game speed color can improve learning outcomes sprint in grade V MI Goddess masyithoh 02 Banyumudal Moga Pemalang District of academic year 2013/2014. Conclusions from the analysis results obtained by researchers, there is an increase in student learning outcomes from initial conditions to cycle I and II, both from an average increase student learning outcomes and value sprint mastery learning outcomes